Improving the Understanding of the Concept and Motivation of Studying Physics with Learning Video Media in Line Learning in SMA Negeri 1 Belik - Suminarsih (Journal of Research in Business, Economics, and Education, 2020)
This study aims to identify and describe the use of instructional video media in increasing understanding of the concept and motivation of learning physics in online learning at SMA Negeri 1 Belik. The research method used a qualitative research approach with descriptive research type. Data collection tools in this study were based on the results of evaluating the implementation of online learning by researchers and questionnaire on student opinions about the use of physics learning video media in online learning that had been implemented. Based on a questionnaire on students' opinions about physics learning video media for online learning, 81 students gave their opinion about the media that students prefer to understand physics concepts with the following results: 63 students chose learning videos, 11 students chose power point media , and 7 students chose the media in word format. Student opinions about the use of instructional video media are as follows: instructional videos really help understand physics concepts as many as 54 students, give an opinion that learning videos are less helpful for understanding physics concepts by 25 students, and those who give opinions on learning videos do not help understanding physics concepts as much 2 students. Whereas in increasing learning motivation, it can be seen from the results of the opinion polls with the following results: 60 students stated that the learning video was an interesting medium, 16 students stated that the learning video was not interesting, and 5 students stated that the learning video was not interesting. From these results it can be concluded that the instructional video media can improve concept understanding and attract students' motivation to learn physics in online learning at SMA Negeri 1 Belik. In order for the learning outcomes to be as expected, infrastructure is needed in the form of smart devices (smart phones) and a stable internet network.